Browning of the subcutaneous adipocytes in diet-induced obese mouse submitted to intermittent fasting. (1st August 2020) - Marinho, Thatiany de Souza; Ornellas, Fernanda; Aguila, Marcia Barbosa; Mandarim-de-Lacerda, Carlos Alberto
Abstract: Purpose: We studied subcutaneous white adipose tissue (sWAT) of obese mice submitted to intermittent fasting (IF). Methods: Twelve-week-old C57BL/6 male mice received the diets Control (C) or high-fat (HF) for eight weeks (n = 20/each). Then, part of each group performed IF (24 h feeding/24 h fasting) for four weeks: C, C-IF, HF, and HF-IF (n = 10/each). Results: Food intake did not show a difference in feeding and fasting days, but HF groups had a high energy intake. IF led to multilocular adipocytes in sWAT (browning), and improved respiratory quotient on the fed day. IF decreased gene expression of Leptin, but increased Adiponectin, β3ar (beta3 adrenoreceptor), and Ucp1 (uncoupling protein). IF enhanced immunostaining of Caspase 3, Pcna (proliferating cell nuclear antigen), and UCP1 in sWAT. IF attenuated pro-inflammatory markers and pro-apoptotic markers in sWAT. Conclusions: IF in obese mice led to browning in sWAT adipocytes, enhanced thermogenesis, an improved adipose tissue pro-inflammatory profile. Graphical abstract: Obese mice have increased body mass and large unilocular adipocytes in subcutaneous white adipose tissue (sWAT). Intermittent fasting leads to adipocyte browning besides reducing the body mass and the adipocyte size, forming multilocular adipocytes in sWAT, which express brown adipocytes signs and attenuate pro-inflammatory markers. Image 1 Highlights: Browning of white adipose tissue is a target to enhance energy expenditure. The intermittent fasting acts on energy metabolism and weight loss. Obese animal adipocytes submitted to intermittent fasting showed browning. Pro-inflammatory markers are lessened in adipocytes because of intermittent fasting.